2016
DOI: 10.1097/moo.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Early death among head and neck cancer patients

Abstract: The present review provides information on the mechanisms leading to early phase mortality (<6 months) after management of HNC. It also reports the incidence of this phenomenon among Finnish and Swedish patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Two previous Swedish studies based on data from 6785 and 9733 HNC patients reported 180-day mortality of 9.8% and 9.5%, respectively [7,8]. These results are consistent with our 180-day mortality of 9.6%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Two previous Swedish studies based on data from 6785 and 9733 HNC patients reported 180-day mortality of 9.8% and 9.5%, respectively [7,8]. These results are consistent with our 180-day mortality of 9.6%.…”
Section: Discussionsupporting
confidence: 93%
“…In nationwide studies of the Swedish and Finnish databases, early mortality at 180 days was about 9-10% [8]. The causes of early mortality may be either tumor-related, patientrelated, treatment-related, or due to perioperative mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the incidence and aetiology of early death among patients with cancers of the head and neck are still scarce, and to our knowledge this is not only the first official report to describe the SweHNCR data on 9733 such patients, but also the first attempt in Europe to investigate early death among patients in a nationwide population-based series. A previous Swedish study based on the data from 6785 such patients during the period 2008–2013 indicated a risk of death within six months of 665 (9.8%) [9]. In the present study we found a slightly reduced risk of early death of 925/9733 patients during the extended period 2008–2015 (9.5%).…”
Section: Discussionsupporting
confidence: 59%
“…Both surgical and oncological treatments usually have acute side effects, but may also result in long-term consequences, and even death. Apart from our own recent review [9], the issue of early death (within six months of diagnosis) among patients with cancer of the head and neck remains poorly explored. Patients with improved survival are often HPV positive, of working age, and have only a few coexisting conditions, and for these patients reductions in treatment have been discussed [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…(6,7) A significant proportion of patients with head and neck cancer die due to the outcomes of malnutrition rather than malignancy itself. (8) Different screening tools have, over the time, been validated such as Nutritional Risk Screening Tool 2002 (NRS 2002), Malnutrition Universal Screening Tool, Nutritional Risk Index, etc. Over the time these tools have aided the health professionals to identify the risk of malnutrition in cancer patients.…”
Section: Introductionmentioning
confidence: 99%